EVALUACIÓN DE UNA FORMULACIÓN ANTIPARDEAMIENTO EN ORITOS (Mussa acuminata) DE DESCARTE PARA LA OBTENCIÓN DE HARINA - Pincay Lictapuson, Angie Mariela (2023)
The main objective of this research project is to evaluate a formula that allows to reduce or control the enzymatic browning caused by the exposure of the pulp of the orite with oxygen, for which a completely randomized block design AXBXC was developed experimentally, which corresponds to eight treatments with three repetitions giving a total of twenty-four treatments, the factors under study are: Factor A (types of acids), factor B (dose of acids), factor C (temperature and drying time). For the tests, the orite were selected, they were washed, peeled and chopped into slices to then be immersed in solutions at different proportions (3g of ascorbic acid and citric acid) (4g of ascorbic acid and citric acid) for thirty minutes, later The orite were taken to the dryer applying different temperatures (40 ° C and 60 ° C) during a period of 48 hours, once the orites were dried they went to the grinding, to determine the effects produced by the twenty-four treatments, the following variables: pH, titratable acidity, humidity, ash, density, colorimetry and microbiological analysis such as: Escherichia coli and total coliforms. Where for the evaluation of the obtained data the Tukey significance test was used (p< 0.05), the same ones that were analyzed within the statistical program STATGRAPHICS. Finding (T3) as the best treatment, in the combination of (4g ascorbic acid/ T 40°C/ t 48) giving the best results: pH 6.04; Titratable acidity % 0.11; Density 0.57 kg/L; Humidity % 10.7; Ash % 2.65, which indicates that this formula is the best option to control enzymatic browning.